Predictive factors for severe maternal morbidity in Brazil: A case-control study - Magalhães, Daniela Mendes Dos Santos [UNESP] (2021)
The maternal mortality or maternal near miss ratio in Brazil reflects the socioeconomic indicators as well as the healthcare quality in some areas of this country, pointing out fragile points in the health services. The aim of this study was to estimate the association of diverse variables related to pregnancy and the occurrence of Near Miss in a population of women who were cared in public maternity wards in Brazil. A case-control study was performed. The association between variables and outcomes was verified through a chi-square test. A multiple analysis was carried out, producing odds ratio (OR) estimates with values of p≤0.25 in the univariate model. The results point to the following risk factors for Severe Maternal Morbidity: non-white (<0.001, OR 2.973), family income of up to two minimum wage salaries (<0.001; OR 2.159), not having a partner (<0.001, OR 2.694), obesity (<0.001, OR 20.852), not having received pre-natal care (<0.001, OR 2.843), going to less than six prenatal appointments (<0.001, OR 3.498), undergoing an inter-hospital transfer (<0.001, OR 24.655), and the absence of labor during admission (<0.001, OR 25.205). Although the results vary, the incidence of women with potential life-threatening complications is high in Brazil, which reinforces the need to universalize more complex interventions as well as coverage of primary care. The presence of precarious socio-economic indicators and unqualified obstetric care were risk factors for Severe Maternal Morbidity.